Correction of tricuspid atresia. - Walker, D R (1975)
Although Fontan and Baudet in 1971 described a physiological correction procedure for tricuspid atresia, very few successful operations have been reported. Two patients corrected 20 and 10 months ago at the Brompton Hospital are presented. These two patients exhibit many of the problems in the management of tricuspid atresia. The first patient aged 20 had undergone three previous palliative operations, a Blalock-Taussig shunt, a Glenn procedure, and an infundibular resection, and therefore presented a number of operative problems. In contrast the second patient, aged 8, whose condition had deteriorated considerably over the previous year, had had no previous surgical treatment. At operation he was found, in addition, to have a partial atrioventricular canal. Details of the operative procedures and the patients' postoperative course are described. The criteria for selection of patients for the Fontan operation are discussed as are the possible long-term hazards of homograft failure, atrial dysrhythmias, and hepatic dysfunction. The successful outcome of these two patients suggests that palliative surgery in infancy should allow for this form of correction in later life.